O papel do Centro de Referência em Saúde do Trabalhador (Cerest) no retorno ao trabalho: discurso dos trabalhadores - Freitas, Karen Grecco de (2020)
Working conditions and requirements influence the life and health of workers, exposing them to accidents and illnesses due to work, which trigger processes of leave, suffering and, in many cases, generate or worsen situations of disability. Thus, return to work (RTW) can be a challenge, considering workers’ new health condition and workplace. The RTW process must involve different social actors, with interaction and collaboration, considering workers’ biopsychosocial aspects and their need to adapt to jobs. Center of Reference in Workers’ Health (Cerest) is an important actor. They are institutions specialized in occupational health that promote intra and intersectoral articulation and contribute considerably to RTW. Thus, this study aimed to analyze the role of Cerest in the RTW process through the workers’ statements, using the Psychodynamics of Work (PW) and the Canadian RT model as assumptions, as well as the Discourse Analysis (DA). This is a qualitative research that used semi-structured individual interviews with workers who returned to work after being off due to an accident or illness at work and who, during the period of absence, were followed by a Cerest from the countryside of the state of São Paulo. Eight workers participated in the study, five were men and three were women, aged between 22 and 66 years. They were bank clerks, production assistants, smelters, logistics assistants, engine rectifiers, cleaning assistants, drivers, and nursing technicians. Time off from work occurred between 2014 and 2018, with a minimum duration of one month and a maximum duration of two years, five resulting from work-related illnesses and three from work accidents. RTW proved to be, in most cases, a difficult experience, in which workers remain without assistance by employers or other institutions. Support came from family, the company’s occupational service, or Cerest. Cerest was acknowledged for providing positive contributions to the leave process and RTW; however, it is limited in the RTW process, acting mainly with guidance for workers and recovery. As a result, actions must be improved, such as communication between team professionals and dialogue with workers; feedback through conducts adopted. Therefore, it is considered that RTW still poses important challenges from the workers’ point of view, signaling suffering and lack of assistance in this experience. Advances are needed in order to strengthen communication, commitment, and co-responsibility of social actors, focusing on the needs of workers and the possibilities of workplace adaptation. In this regard, Cerest can play an important role beyond assistance to workers, acting as triggers and mediators of interactions among the different actors, strengthening communication and decision making so that RTW is gradual, consensual and meets workers’ new health condition.